Reply: Gut microbiome alterations in anti‐NMDA receptor encephalitis: caveats for result interpretation - Gong, Xue; Liu, Xu; Li, Chen; Chen, Chu; Lin, Jingfang; Li, Aiqing; An, Dongmei; Zhou, Dong; Hong, Zhen (Annals of clinical and translational neurology, 2020)
[...]we stated in the “exclusion criteria” that all patients and healthy controls who had antibiotic or probiotic use within the past 3 months were excluded from our study. [...]a recently published study did not show any significant difference of gut microbiome between a small cohort of western patients with anti‐NMDAR encephalitis and healthy control, although the effect of drugs on the gut microbiome could not be excluded in their study since some of the study subjects received immunesuppressives, neuroleptic medication, and probiotics. [...]future studies are needed to enroll more multicenter participants to understand the functional effects of the differences in the gut microbiota on disease initiation, aggravation, and progression.